2013
DOI: 10.1098/rspb.2013.1381
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural fever is a synergic signal amplifying the innate immune response

Abstract: Behavioural fever, defined as an acute change in thermal preference driven by pathogen recognition, has been reported in a variety of invertebrates and ectothermic vertebrates. It has been suggested, but so far not confirmed, that such changes in thermal regime favour the immune response and thus promote survival. Here, we show that zebrafish display behavioural fever that acts to promote extensive and highly specific temperature-dependent changes in the brain transcriptome. The observed coupling of the immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 52 publications
(80 reference statements)
7
93
0
2
Order By: Relevance
“…Moreover, increased level of plasma PGE 2 was correlated with the induction of behavioral fever in dsRNA-challenged zebrafish (Boltaña et al, 2013). These data, together with studies using COX inhibitors strongly indicate that synthesis of PG seems to be necessary for the expression of behavioral fever in ectothermic vertebrates (Fig.…”
Section: Evolutionary Conserved Mechanisms Existing Between Fever Of mentioning
confidence: 54%
See 4 more Smart Citations
“…Moreover, increased level of plasma PGE 2 was correlated with the induction of behavioral fever in dsRNA-challenged zebrafish (Boltaña et al, 2013). These data, together with studies using COX inhibitors strongly indicate that synthesis of PG seems to be necessary for the expression of behavioral fever in ectothermic vertebrates (Fig.…”
Section: Evolutionary Conserved Mechanisms Existing Between Fever Of mentioning
confidence: 54%
“…Grans et al (2012) demonstrated significantly higher IL1b expression in head kidney of rainbow trout (Oncorhynchus mykiss) injected with LPS and subjected to simulated behavioral fever by increasing water temperature of 2.5 C (up to 16.0 C) after injection, as compared to fish that were injected with LPS and kept in constant water temperature of 13.5 C (Grans et al, 2012). The study of Boltaña et al (2013) suggested that behavioral fever induced by injection of zebrafish with synthetic dsRNA (poly I:C) and demonstrated by shift in thermal preference from 29.4 C to 33.1 C, promotes the emergence of a highly specific anti-viral immune response by induction of the transcription of specific genes in brains of zebrafish (Boltaña et al, 2013). This is in accordance with previous observations that higher temperature has a positive effect on viral clearance in fish (Avunje et al, 2012;Novoa et al, 2010).…”
Section: Adaptive Value Of Behavioral Fever In Ectothermic Vertebratesmentioning
confidence: 97%
See 3 more Smart Citations